2022
DOI: 10.3390/su142214897
|View full text |Cite
|
Sign up to set email alerts
|

ICT Adoption Scale Development for SMEs

Abstract: Information systems research lacks a validated scale for assessing and measuring the adoption of information and communication technologies (ICTs) by small- and medium-sized enterprises (SMEs). The relevant literature is limited in studies mainly concentrating on developing country settings. Furthermore, the emergence of new technological elements and increasing digitalization and digital transformation efforts in the last two years have changed how an organization utilizes and adopts ICTs. Therefore, it is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Despite these obstacles, several researchers have proposed several techniques in the literature to help SME owners, and managers overcome barriers to ICT adoption [8]. A measurement scale should be developed for understanding the current status of ICT adoption in an SME [76]. The strategies include those related to infrastructure, the development of human capital, financing, and the judicial process.…”
Section: Strategy To Reduce Gap In Ict Adoptionmentioning
confidence: 99%
“…Despite these obstacles, several researchers have proposed several techniques in the literature to help SME owners, and managers overcome barriers to ICT adoption [8]. A measurement scale should be developed for understanding the current status of ICT adoption in an SME [76]. The strategies include those related to infrastructure, the development of human capital, financing, and the judicial process.…”
Section: Strategy To Reduce Gap In Ict Adoptionmentioning
confidence: 99%
“…The start-up falls under small or medium-sized enterprises (SME) (Budden & Murray, 2021). According to Ozsahin et al (2022), early SME adopters mostly targeted the use of basic ICT, such as website information and electronic mail for communication long before the emergence of social media platforms. However, nowadays, the current trend has shown that social media platforms such as Facebook, Instagram, Snapchat, and YouTube are gaining popularity among SME entrepreneurs (Gilani et al, 2020).…”
Section: Ict For Senior Entrepreneursmentioning
confidence: 99%